2005
DOI: 10.1097/01.meg.0000170927.60979.1d
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis: what is the role of genetics?

Abstract: The aetiology of portal vein thrombosis (PVT) in adults is complex. Risk factors include local precipitating factors and acquired and inherited factors, an area in which there has been much recent progress. Although PVT in the absence of cirrhosis may be regarded as a somewhat different disorder to PVT in the presence of cirrhosis, in both cases most studies support a role of the prothrombin G20210A mutation. Some differences in risk factors observed between different studies may relate partly to referral patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
(28 reference statements)
1
15
0
1
Order By: Relevance
“…In accordance with previously published studies, we found that PVT developed because of several risk factors [9,15,16]. In the restricted analysis, we found a combination of local (56%) and systemic risk factors (50%).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previously published studies, we found that PVT developed because of several risk factors [9,15,16]. In the restricted analysis, we found a combination of local (56%) and systemic risk factors (50%).…”
Section: Discussionsupporting
confidence: 92%
“…Genetic studies have demonstrated that mutations in factor V Leiden and prothrombin are potential genetic factors for portal venous system thrombosis. 10 Unfortunately, we could not perform these 2 analyses because of technical limitations. Intra-abdominal or systemic infections were the predisposing factors in more than one-third of patients with PVT in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, no association between prothrombin gene mutation and PVT was demonstrated in another study [8]. However, the latter was a cross-sectional study and patients with PVT had more severe liver disease than those without PVT [8,15]. The discrepancy in the findings further highlights the importance of patient selection when looking for prognostic risk factors [13].…”
Section: See Article Pages 682-689mentioning
confidence: 92%